Prior exercise in humans redistributes intramuscular GLUT4 and enhances insulin-stimulated sarcolemmal and endosomal GLUT4 translocation - Jonas R. Knudsen; Dorte E. Steenberg; Janne R. Hingst; Lorna R. Hodgson; Carlos Henriquez-Olguin; Zhencheng Li; Bente Kiens; Erik A. Richter; Jørgen F.P. Wojtaszewski; Paul Verkade; Thomas E. Jensen (Elsevier, 2020)
Objective: Exercise is a cornerstone in the management of skeletal muscle insulin-resistance. A well-established benefit of a single bout of exercise is increased insulin sensitivity for hours post-exercise in the previously exercised musculature. Although rodent studies suggest that the insulin-sensitization phenomenon involves enhanced insulin-stimulated GLUT4 cell surface translocation and might involve intramuscular redistribution of GLUT4, the conservation to humans is unknown. Methods: Healthy young males underwent an insulin-sensitizing one-legged kicking exercise bout for 1 h followed by fatigue bouts to exhaustion. Muscle biopsies were obtained 4 h post-exercise before and after a 2-hour hyperinsulinemic-euglycemic clamp. Results: A detailed microscopy-based analysis of GLUT4 distribution within seven different myocellular compartments revealed that prior exercise increased GLUT4 localization in insulin-responsive storage vesicles and T-tubuli. Furthermore, insulin-stimulated GLUT4 localization was augmented at the sarcolemma and in the endosomal compartments. Conclusions: An intracellular redistribution of GLUT4 post-exercise is proposed as a molecular mechanism contributing to the insulin-sensitizing effect of prior exercise in human skeletal muscle.